Talking and Listening edited Essays on the history of sound - Damousi, Joy (ANU Press, 2007)
Historians have, until recently, been silent about sound. This collection of essays on talking and listening in the age of modernity brings together major Australian scholars who have followed Alain Corbin's injunction that historians 'can no longer afford to neglect materials pertaining to auditory perception'. Ranging from the sound of gunfire on the Australian gold-fields to Alfred Deakin's virile oratory, these essays argue for the influence of the auditory in forming individual and collective subjectivities; the place of speech in understanding individual and collective endeavours; the centrality of speech in marking and negating difference and in struggles for power; and the significance of the technologies of radio and film in forming modern cultural identities.